Aging is Associated With an Earlier Arrival of Reflected Waves Without a Distal Shift in Reflection Sites. Issue 9 (29th August 2016) - Phan, Timothy S.; Li, John K.‐J.; Segers, Patrick; Reddy‐Koppula, Maheswara; Akers, Scott R.; Kuna, Samuel T.; Gislason, Thorarinn; Pack, Allan I.; Chirinos, Julio A.
Abstract : Background: Despite pronounced increases in central pulse wave velocity (PWV) with aging, reflected wave transit time (RWTT), traditionally defined as the timing of the inflection point (TINF ) in the central pressure waveform, does not appreciably decrease, leading to the controversial proposition of a "distal‐shift" of reflection sites. TINF, however, is exceptionally prone to measurement error and is also affected by ejection pattern and not only by wave reflection. We assessed whether RWTT, assessed by advanced pressure‐flow analysis, demonstrates the expected decline with aging. Methods and Results: We studied a sample of unselected adults without cardiovascular disease (n=48; median age 48 years) and a clinical population of older adults with suspected/established cardiovascular disease (n=164; 61 years). We measured central pressure and flow with carotid tonometry and phase‐contrast MRI, respectively. We assessed RWTT using wave‐separation analysis (RWTTWSA ) and partially distributed tube‐load (TL) modeling (RWTTTL ). Consistent with previous reports, TINF did not appreciably decrease with age despite pronounced increases in PWV in both populations. However, aging was associated with pronounced decreases in RWTTWSA (general population −15.0 ms/decade, P <0.001; clinical population −9.07 ms/decade, P =0.003) and RWTTTL (general −15.8 ms/decade, P <0.001; clinical −11.8 ms/decade, P <0.001). There was no evidence of an increased effective reflecting distance by either method. TINF was shown to reliably represent RWTT only under highly unrealistic assumptions about input impedance. Conclusions: RWTT declines with age in parallel with increased PWV, with earlier effects of wave reflections and without a distal shift in reflecting sites. These findings have important implications for our understanding of the role of wave reflections with aging.